Evaluation of the needs assessment process of the training courses for the staff of the general sports and youth departments - Shahin Hayati; Haleh Fazel; Lora Chapari (مدیریت و چشم انداز آموزش)
Abstract The purpose of this research is to evaluate the needs assessment process of training courses for the staff of the general sports and youth departments. The research method is applicable in terms of its purpose, and qualitative in terms of implementation, based on the inductive approach. The statistical population of the research includes all professors of sports management, managers, deputy general departments of sports and youth; and sampling was done intentionally or judgmentally; and 15 people in this research were interviewed, and based on the selection of this sample method; sampling done by the researcher was based on personal judgment and study objectives and the nature of the research. After conducting the interviews and using the theoretical saturation technique, interviews were conducted with 12 members of the sample. The evaluation of the design and planning component of training courses is based on the ISO 10015 standard. The data collection tool is a semi-structured interview. Open, central, and selective coding was used for data analysis. According to the results obtained regarding the needs assessment components, there are 6 main categories related to the content of the needs assessment courses, the process of implementing the needs assessment, the participation of the organization members in the course, the timing and prioritization of the basic needs of the organization, and finally the applicability of the topics raised in the period was extracted. Extended abstract Introduction Today, the sustainable development of a country largely depends on the effective use of its productive human resources (Imaneh, 2022). An organization can achieve a competitive advantage if it has competent human resources. If there are efficient, competent, skilled, and experienced managers at the head of the organization and fully aware of management principles and techniques, the success of the organization in reaching its goals is guaranteed. Success in performing managerial roles is more than anything related to the ability and effectiveness of employees and supervisors in terms of skill, knowledge, and attitude (Jafari & Ranaei Kordshouli, 2019). Employee training must be practical, so the first step in employee training planning is training needs assessment. Needs assessment is one of the most important topics expressed in the field of human resources and social services, and it is an analysis that identifies two polar situations; Current situation (where we are), and ideal situation (where we should be) (Mustafezian & Lotfi, 2021). Needs assessment, as an organizational action, is a method that prevents the breakdown and disintegration of employees, current affairs, and patterns of work behavior of the organization. A detailed needs assessment plan may take care of the least fragmentation, separation, and disintegration in the organization (Gooldstion, 2019). It is clear to everyone that performance can be improved by teaching certain knowledge, attitudes, and skills. To identify the most important knowledge, attitudes, and skills; education needs assessment is used (Miller, 2015). Sports organizations such as the General Directorate of Sports and Youth and its subordinate sports boards in each province are involved and supervised as government and service organizations in the field of popular and championship sports development. The complexity of these organizations has increased in recent years, and despite the rules and organizational procedures that are frequently changing, the employees of sports organizations must be constantly trained. The general administrations of Sports and Youth, as the guardians of sports in the whole country, are not excluded; because the general administrations of sports and youth need competent and developed employees in line with other sports organizations and in line with the dynamic changes of the environment in order to continuously achieve its goals. Based on this, the present research seeks to answer the question: how is the evaluation of the needs assessment process of training courses for the employees of the general sports and youth departments? Theoretical Framework Needs assessment Educational needs assessment is a triangular term. Training (any activity to acquire knowledge, skills, or attitude change), needs (gap between current and desired or needed), and assessment (process of identifying needs and prioritizing them). Investing in employee training can achieve better performance. Educational needs assessment is a suitable step to design a suitable and cost-effective educational program by determining specific priorities to achieve specific knowledge, skills, and practice (Yousif et al, 2019). Educational needs Looking at educational planning and its direction, we find that a basic principle is always considered, and that is to use education to meet the need. The most basic step in educational planning is determining the educational needs, and if this step is taken correctly, that is, the identified educational needs are based on reality; the educational programs are also adjusted and implemented based on these needs. They will correspond to reality and are effective in solving individual and organizational issues and problems (Moradi Sarvestani & Zarei, 2017). Kim et al, (2020) conducted a research titled prioritizing the educational needs of school health workers. This study investigated the training needs of health workers in a province of Vietnam. Educational priorities of health workers were analyzed using Borich needs assessment and Locus for Focus model. Based on the results of infectious disease control, education was the highest priority, while the implementation of health promotion programs had a relatively low priority. Based on this, high-priority educational needs can be considered mandatory in the continuing education policy of health workers. Awareness of the importance of health promotion, which is emphasized at the global level, should also be promoted through school health policy. Bae & Roh (2020) investigated the educational needs of Korean nurses in a research. Based on the results obtained from this research, the analysis of educational needs is useful for developing programs to increase the qualifications of nurses. Research methodology The research method is applicable in terms of its purpose, and qualitative in terms of implementation, based on the inductive approach. The statistical population of the research includes all professors of sports management, managers, deputy general departments of sports and youth; and sampling was done intentionally or judgmentally; and 15 people in this research were interviewed, and based on the selection of this sample method; sampling done by the researcher was based on personal judgment and study objectives and the nature of the research. After conducting the interviews and using the theoretical saturation technique, interviews were conducted with 12 members of the sample. The evaluation of the design and planning component of training courses is based on the ISO 10015 standard. The data collection tool is a semi-structured interview. Research findings Open, central, and selective coding was used for data analysis. According to the results obtained regarding the needs assessment components, there are 6 main categories related to the content of the needs assessment courses, the process of implementing the needs assessment, the participation of the organization members in the course, the timing and prioritization of the basic needs of the organization, and finally the applicability of the topics raised in the period was extracted. Conclusion The current research was conducted with the aim of evaluating the needs assessment process of training courses for the staff of the general sports and youth departments. The results of this research are aligned with the results of Kim et al, (2020), Bae & Roh (2020), Cigularo & Dilulio (2020), Bayer et al, (2019), Mircholi & dihim (2019), Vatani et al, (2020), Sanaeinasab & Karamali (2020), Bagheri et al, (2020), Mahmud et al, (2019), Arogundade et al, (2019), Azimi (2019), and Huang & Jao (2016). Cigularo & Dilulio (2020) states that factors such as the inappropriateness of the time of holding classes and the inappropriateness of the training place in terms of distance are among the most important problems raised by learners participating in training courses. Therefore, ignoring the limiting factors on the part of educational program designers can reduce the motivation of learners to participate in educational courses. On the other hand, it should be noted that examining the limiting factors is a very important step in the education process, because the results of this section allow the education managers to design a suitable program according to the existing limitations. According to the results of the research, it is suggested: using the ISO 10015 standard as a tool to guarantee the quality of educational programs enables the organization to evaluate its success rate in designing and compiling educational programs at different time points. In the training section, ISO 10015 proposes a clear road map for management guidance so that senior managers can pay attention to the needs of top, middle, and operational managers as well as employees and meet their needs by changing and modifying training programs. Training should be used simultaneously to help solve organizational problems and increase employee performance.